Suplementação alimentar com vitamina C e desempenho zootécnico de girinos de rã-touro (Rana catesbeiana) - Colombano, Neidison Carneiro [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
The present study evaluated the effects of vitamin C supplementation about the performance indexes of bull frog tadpoles (Rana catesbeiana) with middleweight of 0,0123g ± 0,002g. Distributed in four groups, allocated in 16 boxes of water proof (40 L), the density was of 1 tadpole L-1, The animals received diet supplemented with zero (control), 1,000, 1,500 e 2,000 mg of vitamin C Kg-1 of food, constituting the groups T1, T2, T3 e T4, for 75 days. They were evaluated in this survival rate, tadpole percentage that were metamorphosed in imago, weight gain, specific growth rate and cells differential counting in the blood. The results showed: the best survival rate (93%), the best tadpoles percentage that were metamorphosed in imago (29%), the biggest weight gain of the tadpoles (4,22g), and the best rate of specific growth (6,03%), was observed in the tadpoles that received a supplementation of 2,000mg vit C kg-1 ration. The worst performance was observed in the tadpoles that did not receive vitamin C. Significant difference in the cells differential counting was not observed (Leukocytes and trombocytes) among different treatments. The results suggest that 2000mg of vitamin C Kg-1 is a good option to improve the weight gain indices, specific growth rate, tadpoles percentage that were metamorphosed in imago and survival rate of the frog-bull tadpoles creation

O presente trabalho avaliou os efeitos da suplementação de vitamina C sobre o desempenho zootécnico de girinos de rã-touro (Rana catesbeiana), com peso médio de 0,0123g ± 0,002g. Distribuídos em quatro grupos, alocados em 16 caixas de amianto impermeabilizadas, com capacidade para 40 L de água, na densidade de um girino L-1, os animais receberam dieta suplementada com zero controle), 1.000, 1.500 e 2.000mg de vitamina C kg-1 de ração, constituindo os grupos T0, T1, T1,5 e T2, durante 75 dias. Foram avaliados a taxa de sobrevivência, porcentagem de girinos que se metamorfosearam em imagos, ganho de peso, taxa de crescimento específico e contagem diferencial de células no sangue. Os resultados mostraram que a melhor taxa de sobrevivência (93%), a melhor porcentagem de girinos que se metamorfosearam em imagos (29%), o maior ganho de peso (4,22g), e a melhor taxa de crescimento específico (6,03%/dia), foi observado nos girinos que receberam a suplementação de 2000mg vit C kg-1 ração. O pior desempenho foi observado nos girinos que não receberam vitamina C. Não se observou diferença significativa na contagem diferencial de células (leucócitos, trombócitos) entre os diferentes tratamentos. Os resultados sugerem que 2000/mg de vitamina C Kg-1 é uma boa opção para melhorar os índices de ganho de peso, taxa de crescimento específico, porcentagem de girinos que se metamorfosearam em imagos e taxa de sobrevivência na criação de girinos de rã-touro
Keywords: Girino; Rã touro; Vitamina C; Anfíbio - Metamorfose; Desempenho; Frogs